1992
DOI: 10.1159/000288595
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depression and Anger in Dutch Resistance Veterans from World War II

Abstract: In this study, 147 Dutch Resistance veterans from WW II are evaluated on psychometric instruments for anxiety, depression and anger. Resistance veterans appeared to be more anxious, depressive and angry on these instruments compared to controls from the validation studies of the respective instruments. Veterans currently suffering from PTSD (56%) were significantly more anxious, depressed, and angry than veterans without PTSD. With respect to staying in Nazi concentration camps, which is an extremely severe st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…It should be noted that neither age, education, marital sta tus, favorable medical condition, nor time since cancer diagnosis explained this high distress. Only intrusion as assessed by the IES explained more than a third of the high distress (similar to the finding of Hovens et al [23]). …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It should be noted that neither age, education, marital sta tus, favorable medical condition, nor time since cancer diagnosis explained this high distress. Only intrusion as assessed by the IES explained more than a third of the high distress (similar to the finding of Hovens et al [23]). …”
Section: Discussionsupporting
confidence: 87%
“…Frequent ly, recalling a trauma involves repeating it, with the mem ory of the event appearing to have the properties of an unabsorbed-unwanted object within the memory of the individual [23,31], The Holocaust trauma therefore not only retroactively affects the past but effectively contami nates all subsequent events and thus compromises the healing ability of post-traumatic experiences [22,32].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 20 US studies, 16 were conducted in collaboration with the US Veterans Health Administration (VA). Four approaches were used to identify those with PTSD and comorbidities: assessing for comorbid PTSD and neurocognitive and psychiatric disorders among a general sample of veterans (n = 13), assessing for comorbid PTSD among veterans diagnosed with other neurocognitive and psychiatric disorders (n = 7), assessing for comorbid neurocognitive and psychiatric disorders among veterans diagnosed with PTSD (n = 2), and assessing for comorbid PTSD and neurocognitive and psychiatric disorders among veterans who were prisoners of war (POWs) (n = 2) …”
Section: Resultsmentioning
confidence: 98%
“…The majority of study participants were male and Caucasian; eight studies did not provide information about race, and two studies did not report the sex of the participants …”
Section: Resultsmentioning
confidence: 99%
“…Investigations have shown that even decades after extreme traumatic experiences (WWII, concentration camps) in up to 70% of those questioned, a diagnosis of PTSD prevailed (Kluznik et al, 1986;Hovens et al, 1992;Kuch and Cox, 1992;Guerrero and Crocq, 1994;Neal et al, 1994;Conn et al, 2000;Landau and Litwin, 2000;Port et al, 2001Merckelbach et al, 2003Joffe et al, 2003). The long-term consequences of the traumata experienced earlier on or of trauma reactivation because of current actual events are at the focus here (Heuft, 1999).…”
Section: Discussionmentioning
confidence: 99%